Forecasting household consumption components: A forecast combination approach - Angelia L. Grant; Liyi Pan; Tim Pidhirnyj; Heather Ruberl; Luke Willard (The Australian Government, The Treasury, 2017)
This paper outlines a methodology for forecasting the components of household final consumption expenditure, which is necessary in order to forecast revenue col- lections from a number of different taxes. A forecast combination approach using autoregressive models, regressions on relative prices and the almost ideal demand system developed by Deaton and Muellbauer (1980) is found to offer a more robust forecasting framework than using one of the single models alone. In particular, the combination approach outperforms the almost ideal demand system, which is currently used by the Australian Treasury to forecast the components of consump- tion. The combination framework takes advantage of models that account for the persistence and longer-term trends experienced in a number of the consumption components, as well as shifts caused by evident relative price changes. A forecast combination framework is shown to be particularly useful when forecasting over a three-year forecasting period.
Keywords: 330; Household consumption expenditure; forecast combination